Effect of Cd1-xZnxS Window Layer Incorporation in CdTe Solar Cell by Numerical Simulation - Das N.K.; Sengupta A.K.; Dey M.; Rahman K.S.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cadmium alloys; Cadmium sulfide; Cadmium sulfide solar cells; Cadmium telluride; Copper compounds; Energy gap; II-VI semiconductors; Open circuit voltage; Reflection; Semiconducting cadmium telluride; Semiconducting tellurium compounds; Semiconductor doping; Solar cells; Solar power generation; Transparent conducting oxides; Wide band gap semiconductors; Zinc alloys; Zinc sulfide; Back contact; CdTe solar cells; Doping concentration; Optoelectronic properties; Recombination loss; Solar photovoltaics; Window layer; ZnTe:Cu electron reflector; Semiconducting cadmium compounds